1994
DOI: 10.1002/hec.4730030305
|View full text |Cite
|
Sign up to set email alerts
|

A cost utility analysis of treatment options for gallstone disease: Methodological issues and results

Abstract: The techniques of cost utility analysis (CUA) were used to evaluate the treatment of gallstone disease by open and laparoscopic cholecystectomy and by extracorporeal shockwave lithotripsy (ESWL). The application of the techniques in this context raised three methodological questions which are not satisfactorily resolved in the literature. The first is whether an ex ante or ex post perspective is best adopted for the measurement of quality of life (QoL). The second is the method for converting a short term dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 10 publications
0
58
0
Order By: Relevance
“…Death may not be an effective lower anchor for all health states, however, because participants may be reluctant to gamble with death when the health states describe mild medical conditions. Thus, to discriminate among health states in the high range of the utility scale, it is often necessary to use a temporary health state approach [4,7,[43][44][45][47][48][49][50][51][52]. In this approach, the health states are framed in terms of a specific duration (e.g., 1 month in the current study), with the lower anchor of 0 corresponding to a ''worst'' health state instead of death.…”
Section: Utility Interview Proceduresmentioning
confidence: 99%
“…Death may not be an effective lower anchor for all health states, however, because participants may be reluctant to gamble with death when the health states describe mild medical conditions. Thus, to discriminate among health states in the high range of the utility scale, it is often necessary to use a temporary health state approach [4,7,[43][44][45][47][48][49][50][51][52]. In this approach, the health states are framed in terms of a specific duration (e.g., 1 month in the current study), with the lower anchor of 0 corresponding to a ''worst'' health state instead of death.…”
Section: Utility Interview Proceduresmentioning
confidence: 99%
“…It is possible that this short time frame had an additional effect on the health state values. Cook et al [25]tested the effect of duration on health state values by calculating the values of the reference state using a 12-month and a 12-year time period followed by death. They found no evidence of a significant difference in values.Other research has shown that values are a decreasing function of duration [26].…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies compared conservative management with cholecystectomy. There were six papers that compared outcomes of different interventions such as mini laparotomy, lithotripsy, open cholecystectomy with laparoscopic cholecystectomy 116,117,[136][137][138][139] and one paper compared the different methods of valuing health-related QoL techniques, i.e. visual analogue scale and the standard gamble in measuring people preferences for outcomes of gallstone disease.…”
Section: Quality-of-life Measuresmentioning
confidence: 99%
“…Macafee et al 117 compared early with delayed cholecystectomy and reported utility scores of 0.85 (standard deviation 0.26) for the early group and 0.93 (standard deviation 0.13) for the conventional (delayed) group (QALYs estimated using the EQ-5D questionnaire were calculated 30-35 days after laparoscopic surgery). The final study 138 estimated QALYs for different health states relating to two treatment options using a time trade-off method. The utility score for laparoscopic cholecystectomy was found to be similar to those of the Macafee et al…”
Section: Quality-of-life Measuresmentioning
confidence: 99%